Implementasi Pelayanan Keprotokolan bagi Walikota dan Wakil Walikota di Pemerintah Kota Binjai - Putra Rivanmeta; Isnaini Isnaini; Kaiman Turnip (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The aims of this artickel is to analysis of the implementation and obstacles are there in the implementation of protocol services for the Mayor and Deputy Mayor in the Binjai City Government. The method used is qualitative research with data collection instruments of observation, interviews and documentation studies. And data analysis used descriptive analysis. The results of the study indicate that communication has not gone well and causes coordination not to run optimally between the Protocol and Communication Section of the Regional Secretariat of Binjai City and the event organizing agency. The resources of the Protocol and Communications Section of the Regional Secretariat of Binjai City have not been fully functioning properly. Because employees who are given the responsibility to carry out protocol services have not been able to carry out their duties properly. The attitude of the implementers of the Protocol and Communications Section of the Regional Secretariat of Binjai City has not been implemented properly. The achievement or target of the work program is not yet optimal, which should be realized properly through the service and attitude of the employee's willingness. The bureaucratic structure of the Protocol and Communications Section of the Regional Secretariat of Binjai City is good. The existence of protocol regulations has the aim of providing guidelines for organizing events so that they run in an orderly, neat, smooth, orderly manner in accordance with applicable regulations. Obstacles in research are the lack of coordination and human resources.